Workshop of Improving Teachers’ Competency in Teaching Speaking by Using Buzz Group at SMA Kristen Kalam Kudus Medan. - Poster Sagala; Lina Tarigan; Immanuel Padang; Dorayanti Lumbangaol (JURNAL ABDIMAS MADUMA, 2022)
Speaking ability is an essential tool for communication in a foreign language. Speaking cannot be separated from language learning because it is a productive skill that measures the improvement in learning the language. Speaking a foreign language is effective oral communication that requires the ability to use the language appropriately in social interaction. Principles in teaching speaking are important for improving speaking in the classroom. In order to keep on the intentional communicative class, the teacher should consider those principles. The principles also help the teacher design the appropriate materials. Thus, the teacher should concern with the teaching of speaking comprehension to gain the goals of the teaching and learning process. Buzz groups are teams of four to six students that are formed quickly and extemporaneously to respond to course-related questions, each group can respond to more questions; all groups can discuss the same or different questions. Discussion is informal, and students do not need to arrive at a consensus, but simply exchange ideas. Keywords: Teachers’ Competency, Teaching Speaking, Buzz Group